FAKTOR YANG MEMENGARUHI FIRM VALUE DENGAN MEDIASI CAPITAL STRUCTURE - Anthony, Anthony; Wijaya, Henryanto (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted with the aim of obtaining empirical evidence regarding the effect of Profitability, Sales Growth, and Company Size on Firm Value with Capital Structure as an intervening variable in property sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample used in this study is secondary data which was selected using the purposive sampling method and obtained a sample of 51 companies. In this study, the application used is the SmartPLS 4.0.8.4 program. The results in this study indicate that profitability, sales growth, and company size have no significant effect on firm value, profitability, and sales growth have no significant effect on capital structure, company size, and capital structure have a significant effect on capital structure, capital structure unable to mediate the relationship between profitability, sales growth, and company size on firm value.